SYNTHESIS OF n-OCTYL CINNAMATE USING DCC COUPLING REAGENT ASSISTED BY ULTRASONIC WAVE AND ANTIOXIDANT ACTIVITY TESTS - Devianti, Ananda Endah; Wildan, Achmad; Hanhadyanaputri, Eka Susanti (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
n-Octyl cinnamate is a cinnamic acid derivative that can be synthesized by an esterification reaction between cinnamic acid and n-octanol with the addition of a DCC coupling reagent (N,N'-dicyclohexylcarbodiimide), which is varied into three concentrations equivalent to 1:0.5, 1:0.75, and 1:1 moles of cinnamic acid. Ultrasonic waves assisted in the synthesis of n-octyl cinnamate at 2-8°C for 4 hours. The obtained n-octyl cinnamate was characterized by its organoleptic properties, solubility, melting point, TLC, FTIR-ATR, GC-MS, and antioxidant activity was measured using the DPPH assay. In the results, n-octyl cinnamate was obtained using DCC coupling reagent in 11.85; 14.83; and 35.83 % yields, respectively. This ester dissolves in methanol, ethanol, chloroform, ether, and n-hexane but is insoluble in water. It had a melting point range of 151.4-157.8 ºC. TLC shows that this ester has a different Rf value from that of the reactant. The FTIR spectrum showed suitable bonds with n-octyl cinnamate, as can be seen from its aromatic bands (C=C and C-H), which are characterized by the stretching of C=O and C-O bonds, aliphatic C=C, and aliphatic C-H absorptions. The results from the GC-MS analysis of the targeted compound appeared at 17.184 minutes with a 44.74% purity rate using synthesized n-ocytl cinnamate with the addition of 0,75 equivalent of DCC. The antioxidant activity test using the DPPH assay showed an IC50 value of 93.3375 ppm, indicating strong antioxidant activity. Keywords : antioxidant, esterification, ultrasonic wave, N,N?-dicyclohexylcarbodiimide,  n-octyl cinnamate